Lama, Bonadonna, Garavini, Marianetti, Asor Rosa
descrizione: Lama, Bonadonna, Garavini, Marianetti, Asor Rosa al tavolo della presidenza del seminario precongressuale sui giovani, Ariccia 12-13 aprile 1977.